Comparative Analysis of Intradermal Tuberculin Test and Polymerase Chain Reaction for Bovine Tuberculosis Detection in Punjab, India - Kumar Prajapati, Sudhir; Narang, Deepti; Chandra, Mudit; Tejinder Singh, Sikh; Sharma, Ashwani (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Bovine tuberculosis (bTB) is a zoonotic disease that affects domestic animals, humans, and the wild animals. The purpose of the study was to use the comparative intradermal tuberculin test to diagnose bTB in cattle and to find out the prevalence in unorganized, and organized farm with variation according to age, sex, and breed. Eighty three animals were tested with the use of comparative intradermal tuberculin test across two districts of Punjab, India. Additionally, ante-mortem (nasal swab, n=44) samples were examined using molecular methods. The samples were inoculated on Middlebrook7H10 media after decontamination with 4% NaOH. One sample revealed the presence of acid fast bacilli on microscopic examination. Out of 83 animals examined, 12 were bTB positive reactors. Additionally, gender-wise data analysis revealed higher positivity among cows/heifers (16.17%, 11/68) compared to bulls/bullocks (6.66%, 1/15). Out of the 44 nasal swab samples, 3 samples yielded Mycobacterium kansasii isolates on culture which were further confirmed by species specific PCR. The finding of our study indicates animals of indigenous cattle breed in Ludhiana have a higher prevalence of bTB and variation in breed susceptibility. The presence of non-tuberculous mycobacteria may hamper diagnosing bovine tuberculosis in cattle.